(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents some factors affecting the growth and development of younger school-age children, their content, impact on the body, and the positive and negative results that occur or are expected in their organs and structures. It is intended for teachers of a wide range of general education schools, parents, and future bachelors and masters.